CAUSATIVE CONSTRUCTIONS IN JAVANESE - Qomariana, Yana (Lingual Journal of Language and Culture; Vol 1 No 1 (2016), 2016)
This paper aims at analyzing causative constructions found in Javanese. The data were taken from low register of Javanese spoken in Malang, a city in eastern part of Java Island through observation and note taking techniques. Furtehrmore they were analyzed descriptively against theory of causative construction by Kroeger (2004). The result showed that three types of causative construction: lexical, analytical and morphological causatives exist in Eastern Javanese.
Keywords: causative, lexical, analytical, morphological, Javanese